2014
DOI: 10.1002/ppul.23025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between prenatal and postnatal exposures to folate and risks of allergic and respiratory diseases in early childhood

Abstract: A relatively high maternal serum folate level in mid-pregnancy was associated with a decreased risk of LRTIs and AD in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 32 publications
1
34
4
Order By: Relevance
“…Our results are consistent with those of an Australian Birth Cohort Study which reported that 3rd trimester serum folate levels were not associated with infant atopic dermatitis . In contrast, the Generation R study found slightly increased atopic dermatitis at age 4 in Dutch children born to mothers with 1st trimester plasma folate >16.2 nmol/L (~7 ng/mL), and higher mid‐pregnancy serum folate (>9.5 ng/mL) was associated with decreased atopic dermatitis at 2 years in a South Korean cohort …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our results are consistent with those of an Australian Birth Cohort Study which reported that 3rd trimester serum folate levels were not associated with infant atopic dermatitis . In contrast, the Generation R study found slightly increased atopic dermatitis at age 4 in Dutch children born to mothers with 1st trimester plasma folate >16.2 nmol/L (~7 ng/mL), and higher mid‐pregnancy serum folate (>9.5 ng/mL) was associated with decreased atopic dermatitis at 2 years in a South Korean cohort …”
Section: Discussionsupporting
confidence: 90%
“…25 In contrast, the Generation R study found slightly increased atopic dermatitis at age 4 in Dutch children born to mothers with 1st trimester plasma folate >16.2 nmol/L (~7 ng/mL), 7 and higher mid-pregnancy serum folate (>9.5 ng/mL) was associated with decreased atopic dermatitis at 2 years in a South Korean cohort. 15 The mechanisms behind potential effects of folate on child wheeze are not clear. Potentially, folate may act as an antioxidant 26 or may reduce inflammation via altering the immune system through epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral lower respiratory tract infection (LRTI) in young children continues to be of intense research interest, not least because since it may predispose to asthma and decrements in lung function in later life. Studies of risk factors for severe LRTI found that increased levels of maternal folate in mid pregnancy are associated with a decreased risk of LRTI by 6 months of age, and correlate with cord blood IL‐10 Levels and inversely with cord blood eosinophil counts, while bronchiolitis cases with blood eosinophilia had an increased length of hospital stay (LOS) and were more often mechanically ventilated (24.2%) than those without eosinophilia (7.2%) or without blood counts (0.7%) . Geographic clustering of LRTI cases identified air pollution and poor housing as community level risk factors for wheezing LRTI and viral LRTI, respectively, with higher socio‐economic status reducing the risk .…”
Section: Respiratory Infectionmentioning
confidence: 99%